Disfagia e Intervenção após Esofagectomia - Guimaraes, Michelle Ferreira; Moreira, Márcio José da Silva; Freitas, Andressa Silva de (Distúrbios da Comunicação, 2019)
Kaneoka A, Yang H, Inokuchi H, Ueha R, Yamashita H, Nito T, Seto Y, Haga N. Presentation of oropharyngeal dysphagia and rehabilitative intervention following esophagectomy: a systematic review. Diseases of the Esophagus. 2018; 0:1-11.